Squad selection for cricket team using machine learning algorithms - Malek, Meraj-Bin-; Badhan, Rakib Hasan; Shesir, Mohaiminul Islam; Fakir, Nazmul Haque (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.